Supply strategy configuration in fragmented production systems: An empirical study - Claudia Chackelson; Ander Errasti; Sandra Martinez; Javier Santos (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: Companies survive in saturated markets trying to be more productive and more efficient. In this context, it becomes critical for companies to manage the entire supply network to optimize overall performance. Hence, the supply strategy plays an important role because it influences the way in which production and logistics network has to be configured and managed. This paper explores the benefits obtained configuring different supply strategies adapted to customer needs. Design/methodology/approach: For this purpose a case research from a Tier 2 point of view of the supply chain has been conducted. Findings and Originality/value: The case research demonstrates that a higher service level, less holding costs and increase turnovers can be obtained implementing the adequate supply strategy. Originality/value: There is a scarcity of research specifically focused on applied Supply Chain Principles within network configuration processes. Moreover, there are few empirical studies of global Tier 2 with multiple decoupling points into its supply chain network.
Keywords: 650; Supply chain management; supply strategy; Tier 2; case study